A Study on the Verb Phrases of the Bajau Darat and Bajau Laut Languages in Sabah: A Minimalist Program Analysis: (Kajian Frasa Kerja Bahasa Bajau Darat di Pantai Barat dan Bajau Laut di Sabah : Analisis Kerangka Minimalis) (Jurnal Bahasa, 2021)
This article discusses the unique verbs in the Bajau Darat and Bajau Laut languages by native speakers of the Bajau Darat language in Kampung Keguraan, Kota Belud and Bajau Laut in Kampung Tanjung Kapur, Kudat, Sabah. The Bajau language is the mother tongue of the Bajau people in Sabah. This study aims to identify, describe, and analyse the types of Bajau verbs using the Minimalist Program. The research methods used include field methods, namely interviews, recordings and observations, and the data were analysed using the Minimalist Program. The six respondents interviewed consisted of three native speakers of the Bajau Darat language and three native speakers of the Bajau Laut language. The researchers recorded each respondent's conversation, and each conversation was transcribed and analysed. This analysis focused on the position of verbs in the Bajau Darat and Bajau Laut languages. The results found that the verbs in the Bajau Darat and Bajau Laut languages have tenses. In addition, the Bajau Darat and Bajau Laut languages consist of transitive verbs, intransitive verbs and ditransitive verbs. This study also found that the sentence structure of both the Bajau Darat and Bajau Laut languages is VERB-OBJECT-SUBJECT (VOS). Based on the Minimalist Program approach used, this study has made three findings. First, there is a novel position known as an ObjectP to accommodate this language's VOS position. Second, the verb always moves to the adjunction position of the Tense head. Third, an empty operator (OP) exists to mark the subject in the Bajau language.